Anti-periodic BVP for Volterra integro-differential equation of fractional order 1 < ? ? 2, involving Mittag-Leffler function in the kernel - Aktuglu, Huseyin; Ozarslan, Mehmet Ali (Int Scientific Research Publications, 2016)
In this paper, we consider an anti-periodic Boundary Value Problem for Volterra integro-differential equation of fractional order 1 < alpha < 2, with generalized Mittag-Leffler function in the kernel. Some existence and uniqueness results are obtained by using some well known fixed point theorems. We give some examples to exhibit our results. (C) 2016 All rights reserved.
Keywords: Fractional derivative; fractional integral; Caputo fractional derivative; boundary value problem; Caputo fractional boundary value problem; integral operators; Mittag-Leffler functions